Inovasi Alarm dan Kedisiplinan Masyarakat dalam Manajemen Pembuangan Sampah Rumah Tangga di Perkotaan - Nurcahyo, Rianto; Adiputra, Indra; Pangestu, Febriani (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
Waste is an invaluable or worthless object within the community, while its issue somehow makes a very serious problem ranging from social, economic, even political aspect of daily lives. Being one of most populated developing countries, it is obvious that Indonesia experiences the problem one of which is caused by the people’s unawareness to manage their daily household waste. The purpose of this study is to make a platform to ease the public managing the waste disposal schedule so as not to excessively collect or pile the waste up or even dispose it in improperly, for instance in waterways. Using descriptive analysis method, which is a method used to provide an overview of an object under investigation and collect data without analyzing and drawing conclusions that are open to the public, found the results of this research that it is such a good innovation to be applied within community to discipline people’s attitude against the waste problem. It can be concluded that the community needs support and/or facilities for waste disposal. In addition to improving the performance of cleaning staff, this is due to the lack of attention from the local government, which should be able to follow up the waste problem. Keywords: Alarm system, community discipline, innovation, waste problem Abstrak Sebagai benda yang tak ternilai atau tak berharga, sampah kerap membuat masalah serius di bidang sosial, ekonomi, bahkan politik dalam kehidupan sehari-hari. Menjadi salah satu negara berkembang yang paling padat penduduknya, Indonesia mengalami masalah yang salah satunya disebabkan oleh ketidaksadaran masyarakat untuk mengelola sampah rumah tangga sehari-hari mereka. Tujuan dari penelitian ini adalah untuk membuat platform yang memudahkan masyarakat untuk mengelola jadwal pembuangan sampah agar tidak menumpuk sampah secara berlebihan atau bahkan membuangnya dengan cara yang tidak benar, misalnya di saluran air. Menggunakan metode analisis deskriptif, ditemukan hasil bahwa penelitian ini merupakan inovasi yang baik untuk diterapkan dalam komunitas untuk mendisiplinkan sikap masyarakat terhadap masalah sampah. Dapat disimpulkan pula bahwa masyarakat membutuhkan dukungan dan/atau fasilitas untuk masalah tersebut. Selain dengan upaya meningkatkan kebersihan, kurangnya perhatian dari pemerintah (daerah) seharusnya dapat menindaklanjuti masalah sampah. Kata kunci: Inovasi, kedisiplinan masyarakat, masalah sampah, sistem alarm